Does Transfer to Intensive Care Units Reduce Mortality? A Comparison of an Instrumental Variables Design to Risk Adjustment. Issue 11 (November 2019) - Keele, Luke; Harris, Steve; Grieve, Richard
Abstract : Background: Instrumental variable (IV) analysis can estimate treatment effects in the presence of residual or unmeasured confounding. In settings wherein measures of baseline risk severity are unavailable, IV designs are, therefore, particularly appealing, but, where established measures of risk severity are available, it is unclear whether IV methods are preferable. Objective: We compared regression with an IV design to estimate the effect of intensive care unit (ICU) transfer on mortality in a study with well-established measures of risk severity. Research Design: We use ICU bed availability at the time of assessment for ICU transfer as an instrument. Bed availability increases the chance of ICU admission, contains little information about patient characteristics, and it is unlikely that bed availability has any direct effect on in-hospital mortality. Subjects: We used a cohort study of deteriorating ward patients assessed for critical care unit admission, in 49 UK National Health Service hospitals between November 1, 2010, and December 31, 2011. Measures: Detailed demographic, physiological, and comorbidity data were collected for all patients. Results: The risk adjustment methods reported that, after controlling for all measured covariates including measures of risk severity, ICU transfer was associated with higher 28-day mortality, with a risk difference of 7.2% (95% confidence interval=5.3%–9.1%). The IV estimate of ICU transfer was −5.4% (95% confidence interval=−47.1% to 36.3%) and applies to the subsample of patients whose transfer was "encouraged" by bed availability. Conclusions: IV estimates indicate that ICU care is beneficial but are imprecisely estimated. Risk-adjusted estimates are more precise but, even with a rich set of covariates, report that ICU care is harmful. Abstract : Supplemental Digital Content is available in the text.